MOTIVATION OF VISIT AT THE TOURISM OBJECT OF KINANTAN WILDLIFE AND CULTURE PARK, BUKITTINGGI CITY - Azzahra Fauzia Ulfa; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Motivation is an important factor for prospective tourists in making decisions about tourist destinations to be visited. This study aims to determine the motivation of tourists when visiting the Kinantan Magasatwa and Cultural Park tourism object, Bukittinggi City, West Sumatra. This research uses mixed methods with quantitative descriptive approach. The number of samples in this study were 100 samples who were tourists from the Kinantan Cultural and Magasatwa Park tourism object in Bukittinggi City. In this study, the data collection techniques used were observation, documentation, interviews and questionnaires. Based on the results of the study, the influence of physical motivation got a score of 1,719 with the category of strongly agreeing, cultural motivation getting a score of 980 with the category of disagreeing, social motivation getting a score of 1,350 with the category of not agreeing, and fantasy motivation getting a score of 677 with the category agreeing. Thus, the motivation for tourist visits to the Kinantan Bukittinggi Wildlife and Cultural Park tourism object is to visit on the basis of having physical motivation. Keywords: Motivation, tourists, tourist attraction, Kinantan Bukittinggi Wildlife and Culture Park